Target‐selectivity of parvalbumin‐positive interneurons in layer II of medial entorhinal cortex in normal and epileptic animals. Issue 6 (29th January 2016) - Armstrong, Caren; Wang, Jessica; Yeun Lee, Soo; Broderick, John; Bezaire, Marianne J.; Lee, Sang‐Hun; Soltesz, Ivan
ABSTRACT: The medial entorhinal cortex layer II (MEClayerII ) is a brain region critical for spatial navigation and memory, and it also demonstrates a number of changes in patients with, and animal models of, temporal lobe epilepsy (TLE). Prior studies of GABAergic microcircuitry in MEClayerII revealed that cholecystokinin‐containing basket cells (CCKBCs) select their targets on the basis of the long‐range projection pattern of the postsynaptic principal cell. Specifically, CCKBCs largely avoid reelin‐containing principal cells that form the perforant path to the ipsilateral dentate gyrus and preferentially innervate non‐perforant path forming calbindin‐containing principal cells. We investigated whether parvalbumin containing basket cells (PVBCs), the other major perisomatic targeting GABAergic cell population, demonstrate similar postsynaptic target selectivity as well. In addition, we tested the hypothesis that the functional or anatomic arrangement of circuit selectivity is disrupted in MEClayerII in chronic TLE, using the repeated low‐dose kainate model in rats. In control animals, we found that PVBCs innervated both principal cell populations, but also had significant selectivity for calbindin‐containing principal cells in MEClayerII . However, the magnitude of this preference was smaller than for CCKBCs. In addition, axonal tracing and paired recordings showed that individual PVBCs were capable of contacting both calbindin and reelin‐containing principal cells. In chronically epileptic animals, we found that the intrinsic properties of the two principal cell populations, the GABAergic perisomatic bouton numbers, and selectivity of the CCKBCs and PVBCs remained remarkably constant in MEClayerII . However, miniature IPSC frequency was decreased in epilepsy, and paired recordings revealed the presence of direct excitatory connections between principal cells in the MEClayerII in epilepsy, which is unusual in normal adult MEClayerII . Taken together, these findings advance our knowledge about the organization of perisomatic inhibition both in control and in epileptic animals. © 2015 Wiley Periodicals, Inc.